A Retrospective Study of First-Line Therapy Involving Immune Checkpoint Inhibitors in Patients With Poor Risk Metastatic Renal Cell Carcinoma - Jo, Hyunji; Hong, Joohyun; Kim, Hongsik; Kim, Hye Ryeon; Kwon, Ghee Young; Kang, Kyung A.; Park, Sung Yoon; Kim, Chan Kyo; Park, Byung Kwan; Chung, Jae Hoon; Song, Wan; Kang, Minyong; et al. (Frontiers in Oncology, 2022)
Purpose: Patients with poor-risk metastatic renal cell carcinoma (mRCC) rarely respond to first-line tyrosine kinase inhibitors (TKIs), including sunitinib, and have a very poor prognosis. In recent years, combination therapy involving immune checkpoint inhibitors (ICIs) has demonstrated superior efficacy to sunitinib in poor-risk disease. Methods: In a retrospective study using a cancer chemotherapy registry, 206 consecutive patients with mRCC in the first-line setting were identified between Oct 2019 and Dec 2020. Sixty-one patients had a poor-risk mRCC and were treated with TKI monotherapy (n = 36), nivolumab plus ipilimumab (n = 16), or pembrolizumab plus axitinib (n = 9). Endpoints included overall survival (OS), progression-free survival (PFS), response rate (RR), and safety. Results: At the time of initiating first-line therapy, the patients’ median age was 61 years and the median number of International Metastatic RCC Database Consortium (IMDC) risk factors was 3 (range, 3-5). During a median 23.0 months of follow-up, the median OS was 24.3 months with ICI-based combinations and 14.8 months with TKI monotherapy, and the median PFS periods were 9.3 months and 3.4 months, respectively. An objective response occurred in 60% of the patients receiving ICI-based combinations and in 19% of those receiving TKI monotherapy (P = 0.001). In the multivariate regression model, number of IMDC risk factors and ICI-based combination therapy were independent prognostic factors for PFS. All-causality grade 3 or 4 adverse events were 44% for ICI-based combinations and 50% for TKI monotherapy. Conclusions: Among patients with poor-risk mRCC, first-line ICI-based therapy showed significantly longer OS and PFS, as well as a higher RR, than TKI monotherapy.